Measuring Transducer for Air Gap Capacitive Sensor in Hydrogenerator - A. S. Levytskyi; I. O. Zaitsev; V. O. Bereznychenko; O. E. Sukhorukova (Приборы и методы измерений, 2020)
One of the most important parameters of powerful hydro generators (HG) is the air gap between the rotor and the stator, and its deviation from the set norms is a defect that can lead to serious accidents. Therefore, the size and shape of the gap must be monitored both during inspections and during operation of the machine. The aim of this paper was to develop a secondary measuring transducer providing accuracy and resolution for a capacitive gap sensor formed by coplanar parallel electrodes.It is shown that the reliability and safety of operation of powerful HG inextricably depend on the timely detection of their defects, especially during operation. One of the most important parameters of the HG is the air gap between the rotor and the stator, and its deviation from the set norms is a defect that can lead to serious accidents. Therefore, the size and shape of the gap must be monitored both: during inspections and during operation of the machine. The paper discusses the features of measuring the air gap in a powerful HG, as well as existing modern methods and means of measurement.It is shown that for measuring the gap in capsule HG, one of the most suitable means is a meter, which includes a capacitive sensor mounted on a central bore of the stator core. Commercially available gap meters with capacitive sensors are not suitable for use on HGs. Commercially available meters with capacitive sensors, by their certain characteristics, are not always suitable for use on HGs.A secondary measuring transducer with improved characteristics is proposed for a capacitive gap sensor formed by coplanar parallel electrodes.The converter is developed on the basis of a balanced compensation bridge measuring circuit. The control action in the device is formed by the phase of the unbalancing signal.The structural diagram of the converter is presented and the algorithm of its operation is described. The process of forming a measuring output signal proportional to the sensor working capacitance in the circuit is considered.The use of a capacitive sensor with coplanar parallel electrodes and the proposed secondary measuring transducer will ensure high accuracy and resolution when measuring the air gap.